Implementasi Metode STIFIn dalam Proses Menghafal Al-Quran Santri Remaja di Ma’had Tahfiz Baitul Quran Aceh Besar - Iqramullah Iqramullah (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
The STIFIn method is one of the learning methods whose learning process focuses on a child's genetics, in its implementation this method offers a quick memorization solution that is done starting before the memorization process. The purpose of this research itself is to see how the implementation, impact and opportunities and challenges of the implementation of STIFIn methods in the process of memorizing the Qur'an. This research uses a qualitative approach and the research subjects of Headmaster, Tahfizh Teacher and Students Of Ma'had Tahfizh Baitul Quran Aceh Besar. Data collection is done by observation, interview and documentation. The results showed that, to apply the STIFIn method in the process of memorizing the most established students first carried out finger print, preparing tools and means and explaining the technical in memorization, after feeling ready to enter the implementation of the method in the classroom. The resulting impact through the implementation of this method is the increasing memories of students and students motivated in memorizing the Qur'an. In its application there are opportunities and challenges, among the opportunities generated is the cooperation with the Director of STIFIn Aceh and the assistance of outside experts who contribute to the implementation of this method. The challenges include relatively expensive administrative processes, self-adjustment and tools (media) as well as inadequate means.